(untitled) (Emergency Care Journal, 2019)
On the afternoon of 18 January 2017, a major avalanche occurred on Gran Sasso d’Italia massif, destroying an hotel in Rigopiano, and killing twenty-nine people. A staff of psychologists trained in emergency psychology was involved to assist the families of the missing persons without ever abandoning them for eight consecutive days. Particular care was posed to identify an appropriate setting where families and psychologists could interact, favoring emotional containment and protection of intimacy in moments of intense pain. It was considered paramount that the team shared their intervention method, and that nobody operated individually, because this would support both families and members of the professional group. The long waiting for news about the missing persons’ fate was a suspended time, during which the psychologists engaged in emotional rescue were called to express their empathy understanding and sharing silence. Once the bodies were retrieved, the recognition of corpses required the sharing of a common operational strategy to face lucid or contradictory communications, and the alternate feelings of disbelief, anger, or guilt. As a consequence of the Rigopiano tragedy, in the year 2018 the Abruzzo region wrote a new plan for maxi health emergencies, recognizing psychological suffering among the needs to be met in case of disaster.